Application of The Teams Games Tournament Learning Model in Improving Science Learning Outcomes in Elementary School Students - Marlina; Halmuniati; Irnawati (Jurnal Wawasan Sarjana, 2024)
This research can be carried out with the aim of improving science learning outcomes using the TGT (Teams Games Tournament) learning model. This type of research is classroom action research (PTK), which is divided into four phases: planning, carrying out, observing and evaluating, and reflecting. Descriptive analysis is the data analysis method used in this study to give a general picture of the change in student learning outcomes. taught utilizing the Teams Games Tournament (TGT) learning approach, which includes learning test results and observation sheets of instructor and student activities. Learning objectives for science in class V at SDN 1 Wolasi. The Teams Games Tournament (TGT) learning approach has seen a notable growth in applicability. The pre-cycle to cycle II results demonstrate this; pre-cycle scores averaged 63.33 with a learning completeness of 61.11%, while learning completeness after the first cycle averaged 77.78 with a 70% score. Following cycle II, learning completeness averaged 87.5, or 83.33%. Between pre-cycle I and cycle II, there was an increase of 45.34%. in order for Wolasi 1 Elementary School's student learning outcomes to be enhanced by the TGT learning approach.